Android-Based Geographic Information System Tourism of Samarinda City - Aca Al Ahwa; Suswanto Suswanto; F. V. Astrolabe Sian Prasetya (Journal of Geomatics Engineering, Technology, and Science, 2022)
This research is motivated by the tourism potential of Samarinda which is actually very good, but this potential has not been fully utilized by the city government and the private sector. So that people are less interested in traveling in Samarinda. Therefore, the purpose of this research is to build an android-based regional tourism information system for Samarinda City as a source of information to find out what tourist objects are owned by Samarinda City. This study uses spatial data in the form of location coordinates, addresses and non-spatial data as well as supporting information in the form of tourist names, categories, types of tours, addresses. Making this Android-Based Samarinda City Tourism Geographic Information System using Google Maps as a base map. The results of this study are to simplify data management for the general public, the test results of 60% of respondents answered agree, 34% of people answered strongly agree, 4% of people answered less agree, 2% of people answered disagree, 0% of people answered strongly disagree, and the results of the validation test using Pearson's product moment correlation model using SPSS with the number of rcount>rtable all valid data.